Abnormal cervical smears: are we in for an epidemic?. Issue 6391 (20th August 1983) - Wolfendale, M R; King, S; Usherwood, M M
Abstract : A retrospective study was conducted to examine the pattern of a disturbing increase in abnormal cervical smears in one health district. Past records over fifteen years (1965-79) were analysed to produce pick up rates according to age, screening state, severity of lesion, and area of residence. Main findings included an increased pick up rate in unscreened (5.8 to 12.9/1000 smears) and screened (0.9 to 3.6/1000 smears) women. The order of increase was proportionately much higher in women under 40 years. The only significant epidemiological variable in the catchment area was a substantial population increase, overweighted by the younger age groups. The principal conclusion of the study was that the increased pick up rates of abnormal cervical smears in the district reflected a true increase in the incidence of premalignant lesions of the cervix. Screening efforts aided by computerisation should be examined nationwide in order to reach high risk groups and thus try to prevent an increase in carcinoma of the cervix.